Will the ASEAN Intergovernmental Commission of Human Rights (AICHR) Grow Its Teeth? - Olivia, Yessi (Jurnal Hubungan Internasional, 2014)
ASEAN Intergovernmental Commission on Human Rights (AICHR) was established in 2009. Its main functions are to promote and to protect human rights and fundamental freedoms of the people of ASEAN. Since the beginning of its formation, AICHR has been criticized for being a toothless institution. This is because of the weak nature and power given to this body. This paper analyzes what the future lies for AICHR. Will it continue to become a partial human rights mechanism or will it transform into an independent human rights body. It is argues that several factors will determine the future of AICHR. Firstly, is the ability of AICHR in internalizing human rights norms. Secondly, is the commitment of ASEAN countries to human rights promotion and protection. Thirdly, is the endless endeavor coming from civil society not only criticizing but also supporting AICHR. The structure of this paper is as follows. The first section elaborates theories on why states join or signing human rights regime or treaties. This will be followed by providing a brief profile of ASEAN and emphasizing on the organization norms. Next, the paper explains the anatomy of AICHR and provides brief comparison between AICHR and several regional human rights systems. The origin and the development of AICHR are discussed in the next section, followed by analyzing the future of AICHR.